30. EVALUATION OF THE EFFECTIVENESS OF PHYSIOTHERAPY IN MUSCULOSKELETAL PAIN AND JOINT PAIN PATIENTS OF LEVEL 2 FIELD HOSPITAL NO. 6 (Tạp chí Y học Cộng đồng, 2025)
Objective: This study aimed to evaluate the effectiveness of physiotherapy in managing musculoskeletal and joint pain at Vietnam’s Level 2 Field Hospital No. 6.Subjects and Methods: A total of 109 outpatients with musculoskeletal or joint pain were enrolled and treated with physiotherapy, involving at least three of the following techniques: shortwave therapy, therapeutic ultrasound, electrical stimulation, acupuncture, and infrared light therapy. Each patient underwent a minimum of 10 treatment sessions. Pain levels were assessed using the Visual Pain Scale (VPS) at three time points: Day 0 (baseline), Day 5, and Day 10.Results: Pain levels significantly decreased over time, with mean VPS scores reducing from 6.34 ± 1.77 (Day 0) to 4.09 ± 1.41 (Day 5), and further to 1.21 ± 1.13 (Day 10) (p < 0.001 for all comparisons). No adverse effects were reported.Conclusion: Multimodal physiotherapy proved to be an effective and safe approach in alleviating musculoskeletal and joint pain in the resource-constrained setting of a field hospital.
Keywords: Physiotherapy; musculoskeletal pain; joint pain; field hospital; multimodal therapy.